2016
DOI: 10.1093/ajcp/aqw139
|View full text |Cite
|
Sign up to set email alerts
|

Significant Reduction in Preanalytical Errors for Nonphlebotomy Blood Draws After Implementation of a Novel Integrated Specimen Collection Module

Abstract: Implementation of a customized specimen collection module led to a significant reduction in preanalytical errors. Improved compliance with the system may lead to further reductions in error rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…The reason for this might be that the wards use glucose meters to measure blood sugar. A more standardised method of using a new request system has shown significant results for minimising these PAEs . Although we did not get high PAE results in the coagulation tests, a study conducted in Italy reported almost twice the amount.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The reason for this might be that the wards use glucose meters to measure blood sugar. A more standardised method of using a new request system has shown significant results for minimising these PAEs . Although we did not get high PAE results in the coagulation tests, a study conducted in Italy reported almost twice the amount.…”
Section: Discussioncontrasting
confidence: 63%
“…Several studies have reported different practical interventions for reducing PAEs, such as introducing a collection module and introducing educational training programmes for staff. These interventions have had effects on reducing PAEs in the studied departments (). Dorotic et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaufman and colleagues found a residual WBIT error rate of one in 15,000 with ePPID attributable to three deviations: utilizing wristbands not affixed to a patient, failing to immediately apply labels generated at the bedside to samples, and affixing another patient's wristband to the patient. This report confirms other single‐center reports detailing error rates before and after implementation of ePPID technology for the collection of blood samples (with a 1.7‐ to 5.5‐fold safety margin) . Success with ePPID has also been reported to reduce errors in pathology samples from an endoscopy suite, to reduce wrong patient or wrong product errors in a nuclear pharmacy, and to reduce wrong medication dispensing and administration .…”
supporting
confidence: 83%
“…This report confirms other single-center reports detailing error rates before and after implementation of ePPID technology for the collection of blood samples (with a 1.7-to 5.5-fold safety margin). [19][20][21] Success with ePPID has also been reported to reduce errors in pathology samples from an endoscopy suite, 22 to reduce wrong patient or wrong product errors in a nuclear pharmacy, 23 and to reduce wrong medication dispensing and administration. 24,25 The publications of a few before-after implementation studies of ePPID, [19][20][21] and the reduction in WBIT rates over time, 12 suggest that this technology is just starting its move into health care.…”
mentioning
confidence: 99%